Specific gene expression in unmyelinated dorsal root ganglion neurons in nonhuman primates by intra-nerve injection of AAV 6 vector - Moeko Kudo; Sidikejiang Wupuer; Maki Fujiwara; Yuko Saito; Shinji Kubota; Ken-ichi Inoue; Masahiko Takada; Kazuhiko Seki (Molecular Therapy: Methods & Clinical Development, 2021)
Adeno-associated virus 6 (AAV6) has been proposed as a potential vector candidate for specific gene expression in pain-related dorsal root ganglion (DRG) neurons, but this has not been confirmed in nonhuman primates. The aim of our study was to analyze the transduction efficiency and target specificity of this viral vector in the common marmoset by comparing it with those in the rat. When green fluorescent protein-expressing serotype-6 vector was injected into the sciatic nerve, the efficiency of gene expression in DRG neurons was comparable in both species. We found that the serotype-6 vector was largely specific to the pain-related ganglion neurons in the marmoset, as well as in the rat, whereas the serotype-9 vector resulted in contrasting effects in the two species. Neither AAV6 nor AAV9 resulted in DRG toxicity when administered via the sciatic nerve, suggesting this as a safer route of sensory nerve transduction than the currently used intrathecal or intravenous administrative routes. Furthermore, the AAV6 vector could be an optimal serotype for gene therapy for human chronic pain that has a minimal effect on other somatosensory functions of DRG neurons.